Jenis-Jenis Lamun (Seagrass) Di Perairan Pantai Negeri Hutumuri Kecamatan Leitimur Selatan Kota Ambon (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2023)
Seagrass is a very important plant that grows in coastal areas. The beach of Hutumuri village which is bordered by the open sea can affect the existence of seagrass beds and there are housing along the coast so that it allows for community activities on the beach. The purpose of this study was to determine the types of seagrass in the coastal waters of Hutumuri Village, Ambon City. The data collection method used was the cruising method which was carried out to obtain the types of seagrass at the research location. Sampling of seagrass was carried out at maximum low tide in November 2022. In this study, 3 types of seagrass were found, namely Thalassia hemprichii, Halodule pinifolia and Cymodocea rotundata. Thalassia hemprichii has flat leaves, longitudinal leaves like lines, there are brown lines on the leaves, leaf blades are slightly curved, 5-20 cm long leaves, 4 cm wide leaves. The tips of the leaves are rough and rounded. Each stand has 3-4 leaves. Each node contain 1 root surrounded by small dense hairs. Halodule pinifolia leaves are flat, narrow like needles, leaf tips are rounded. Leaf blade length 6-15 cm, leaf blade width 0.1-0.2 cm. Each stand has 1-2 leaves. each node has a number of small roots, the distance between nodes 1-3 cm. Cymodocea rotundata has flat leaves, leaf blade length 7-15 cm, blade width 2-4 cm. Each stand has 2-4 leaves. Between rhizomes there are nodes. Each stand and node has 1-2 roots. The distance between nodes is 2 cm.